Cochlear Implantation in Pediatric Patients With Enlarged Vestibular Aqueduct: A Systematic Review. (7th July 2021) - Benchetrit, Liliya; Jabbour, Nicolette; Appachi, Swathi; Liu, Yi‐Chun; Cohen, Michael S.; Anne, Samantha
Abstract : Objective(s): To describe cochlear implantation (CI) outcomes, with speech perception, auditory, language, and parent‐reported auditory and speech behaviors, in children with an enlarged vestibular aqueduct (EVA) and incomplete partition type 2 (IP‐II) and compare to control children without inner ear malformations (IEMs) and to determine cerebrospinal fluid gusher rates and effect on outcomes. Study Design: Systematic review and meta‐analysis. Methods: MEDLINE, Embase, Cochrane, and CINAHL databases were searched from inception to February 2020. Studies reporting relevant outcomes in children with EVA or EVA + IP‐II and controls without IEMs undergoing CI were included. Mean differences in speech perception, auditory, and language scores between cases and controls were meta‐analyzed. Gusher rates were determined by proportion meta‐analyses. Results: Of 214 identified articles, 42 met inclusion criteria, evaluating 775 cases and 2, 191 controls. Of –cases, 578 (74.6%) had EVA and 197 (25.4%) had EVA + IP‐II. Cases showed a significant improvement in speech perception, auditory and language performance, comparable to controls. Parent‐reported auditory and speech production behaviors outcomes were positive among cases and comparable to controls. Pooled gusher proportions in EVA and EVA + IP‐II cases were 27.7% (95% CI: 17.6–39.1) and 48.6% (95% CI: 28.6–69.0), respectively, with a proportion difference of 20.9% (95% CI: 11.0–30.1). Gusher occurrence did not impact speech perception or language outcomes. Conclusion: Outcomes in children with EVA or EVA + IP‐II undergoing CI are favorable and largely comparable to outcomes in children with hearing loss undergoing CI without IEMs. Intraoperative gusher is more prevalent among children with EVA + IP‐II as compared to iEVA. Gusher does not influence speech perception and language development outcomes. Level of Evidence: NA Laryngoscope, 132:1459–1472, 2022